Experience of sexual harassment in public transport among female health science students: A cross sectional study of Kathmandu, Nepal - Mishra, D.; Lamichhane, J. (Journal of Manmohan Memorial Institute of Health Sciences, 2018)
Background: Sexual harassment on public transport is an everyday occurrence for millions of girls and women around the globe. With the skyrocketing population of Kathmandu valley public transport has been facing enormous pressure. The major victims of these harassments happens to be college going girls and working women as they tend to travel more in public transports. This study sought to determine the prevalence and factors responsible for sexual harassment in public transport among female health science students. Methods: A descriptive cross-sectional study was carried out among 396 female health science students studying in Manmohan Memorial Institute of Health Sciences using self-administered structured questionnaire. Participants were selected through stratified random sampling method. Results: The prevalence of sexual harassment among female health science students was found to be 79.6%. Physical harassment was the most prominent type of harassment (67.1%) followed by verbal (61.2%) and non verbal 34.6%. After the experience of sexual harassment, 44.6% scolded the harasser, 29.1% kept silent, 17.3% dropped at nearest bus station whereas remaining 9% reacted in other different ways. Overcrowding was considered as main reason for sexual harassment by 69.2% of the participants. 36.8% of female students didn’t use any precautionary methods whereas 32.6% avoided going out alone at night. Conclusion: The study reveals that the prevalence of sexual harassment is significantly high. With increasing population and limited vehicles people are left with no option rather than travelling in the overcrowded vehicles where the chances of experiencing various sorts of sexual harassments are very high. In order to address this emerging issue, prompt and appropriate intervention should be taken by government, public and especially the status of women must be raised in society. JMMIHS.2018;4(1):20-32